2019
DOI: 10.1177/0963689719854363
|View full text |Cite
|
Sign up to set email alerts
|

Cells Involved in Urethral Tissue Engineering: Systematic Review

Abstract: The urethra is part of the lower urinary tract and its main role is urine voiding. Its complex histological structure makes urethral tissue prone to various injuries with complicated healing processes that often lead to scar formation. Urethral stricture disease can affect both men and women. The occurrence of this pathology is more common in men and thus are previous research has been mainly oriented on male urethra reconstruction. However, commonly used surgical techniques show unsatisfactory results because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Results from the study of Orabi and De Filippo demonstrated that collagen scaffolds seeded with cells can be used for longer urethral replacement [ 12 , 18 ]. Therefore, the scaffolds and seeded-cells are the two critical components of tissue engineering urethra [ 19 21 ]. A good blood supply and sterile environment, which can only be provided in good animal models, are essential for the survival both of the scaffolds and the seeded-cells after its transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the study of Orabi and De Filippo demonstrated that collagen scaffolds seeded with cells can be used for longer urethral replacement [ 12 , 18 ]. Therefore, the scaffolds and seeded-cells are the two critical components of tissue engineering urethra [ 19 21 ]. A good blood supply and sterile environment, which can only be provided in good animal models, are essential for the survival both of the scaffolds and the seeded-cells after its transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…They were followed up from 36 to 76 months postoperatively. Serial radiography and endoscopy revealed a wide, patent urethra with a median end maximum urinary flow rate of 27.1 ml/s (range [16][17][18][19][20][21][22][23][24][25][26][27][28]. Urethral biopsies at 3 months postimplantation revealed a normal histological architecture [45].…”
Section: Key Pointsmentioning
confidence: 98%
“…Scholars have made many attempts to select scaffold materials and cells to achieve this goal. Nevertheless, the macro-and microstructure of the scaffold also plays a crucial role in urethral regeneration [17][18][19]. In this review, we divide urethral grafts into two types according to their structures: scaffold-free and scaffolded grafts.…”
Section: Biomimetic Grafts For Urethral Reconstructionmentioning
confidence: 99%